Equity & Middle Grades Organizational Structures: Echoes of the Past, Influences on the Present, Hopes for the Future - Gayle Andrews (Middle Grades Review, 2023)
Fostering a sense of belonging is fundamental to recommended organizational structures in middle grades schools including interdisciplinary teams, advisory relationships, flexible instructional schedules, and heterogeneous grouping. Middle grades educators must ensure that organizational structures support a sense of belonging and also problematize the very idea of “belonging,” actively countering and disrupting white supremacy culture and colonizing forces that can make “belonging” conditional and available only for those who accept systemic oppressive forces without question or complaint. This essay contends that key organizational structures in middle grades schools can be designed and enacted to infuse equity orientations and culturally sustaining approaches and practices into the daily lives of educators and young adolescents.